Seizure Outcome in Adult Patients with Isolated Focal Cortical Dysplasia in Modern Era - Tahmazoğlu, Burak; Kartum, Tufan Agah; Kemerdere, Rahşan; Sayyahmelli, Sima; Yeni, Seher Naz; Tanrıverdi, Taner (Cerrahpaşa Medical Journal, 2020)
Objective: Focal cortical dysplasia (FCD) is the most common cause of focal epilepsy in children and adults. The long-term seizure outcome has been reported in children, but very limited data are available for adults. The aim of this retrospective study is to provide long-term seizure outcome in adults with isolated FCD. Methods: A total of 23 adult patients operated on type I and II FCD were included. Medical history, seizure semiology, and radiological features were reviewed from the patients’ charts. Long-term seizure outcome was obtained with telephone interviews and last follow-up data available in archive. Results: At the last follow-up, 16 patients (69.6%) were totally seizure free even without aura and 7 patients (30.4%) continued to have seizure. Both type I (75%) and type II FCD (63.7%) showed higher seizure-free rate, and no significant difference was found (p=0.6). Conclusion: Surgery is safe and results in high seizure-free rate in adult patients with isolated FCD, but it is not enough because we cannot still explain why some patients continue to have seizure after complete removal of the dysplastic area. Cite this article as: Tahmazoğlu B, Kartum TA, Kemerdere R, Sayyahmelli S, Yeni SN, Tanrıverdi T. Seizure Outcome in Adult Patients with Isolated Focal Cortical Dysplasia in Modern Era. Cerrahpaşa Medical Journal 2020; 44(2): 86-92.